Essential oil from Cymbopogon flexuosus as the potential inhibitor for HSP90. (2018) - Gaonkar, Roopa; Shiralgi, Yallappa; Lakkappa, Dhananjaya B.; Hegde, Gurumurthy
Graphical abstract: Highlights: The essential oil of Cymbopogon flexuosus or lemongrass oil (LO) is reported. Essential oil of C. flexuosus significantly suppresses the HSP90 gene expression. Increased expression of HSP90 gene by citral and geraniol in HEK-293 cells. Inhibition of HSP90-ATPase acitivity by the essential oil of C. flexuosus. Abstract: The essential oil of Cymbopogon flexuosus or lemongrass oil (LO) is reported to have antibacterial, antifungal and anticancerous effects. HSP90 is one of the major chaperones responsible for the proper folding of cancer proteins. In this paper we show that the essential oil of C. flexuosus significantly suppresses the HSP90 gene expression. The cytotoxicity of the compounds was tested by MTT assay and the gene expression studies were carried out using HEK-293 and MCF-7 cells. Also we tested the efficacy of the major component of this essential oil viz. citral and geraniol in inhibiting the HSP90 expression. The oil was found to be more cytotoxic to MCF-7 cells with different IC50 values for the oil (69.33 μg/mL), citral (140.7 μg/mL) and geraniol (117 μg/mL). The fold change of expression was calculated by RT-qPCR using ΔΔCt (2 ^−ΔΔCt ) method and it was 0.1 and 0.03 in MCF-7 cells at 80 μg/mL and 160 μg/mL of LO. Western blot results showed suppression of HSP90 protein expression and HSP90 – ATPase activity inhibition was also observed using LO. This study shows the anticancer mechanism exhibited by the essential oil of C. flexuosus is by the inhibition of the important chaperone protein HSP90.